Anti-Acne Patch Formulation Silkworm Cocoon Waste with HPMC and PVP Variations - Ulfa, Maria; Fatmawaty, Aisyah; Dambur, An M.R. (Indonesian Journal of Pharmaceutical Science and Technology, 2023)
Some topical preparations for acne have been developed in the form of gels and creams. However,it is still rarely developed in the form of a patch dosage form. Waste from silkworm cocoons has theactivity of inhibiting the growth of acne-causing bacteria, can be formulated into patch preparations.This study aims to formulate anti-acne patches from silkworm cocoon waste with variations of HPMCand PVP. The formulation of the anti-acne patch from silkworm cocoon waste was made by mixingthe lyophilisate of silkworm cocoon waste with a patch base with variations of HPMC and PVP. Theformulations were divided into 3 with different concentrations of HPMC and PVP additives, namelyformulas 1 (4:1), 2 (2,3:1), and 3 (1:1), respectively, The evaluations carried out included organolepticexamination, patch thickness, weight uniformity, fold resistance, moisture absorption, drying shrinkage.The results obtained showed that the concentration of the combination of HPMC and PVP polymersin the patch preparation gave different results from all evaluations that had been carried out, includingorganoleptic evaluation, weight uniformity, fold resistance, and drying shrinkage were in accordancewith the requirements of a good patch. The optimum concentration of the combination of HPMC andPVP as a polymer in the anti-acne patch preparation from silkworm cocoons is formula 2 with a ratioof (2,3:1) as novelty in this study.